(3fgGjI GdShd aj efGbH hUGjG GdQShds - (3eMeO Hf GdfGUQ Hf eMeO Hf GdfGUQs
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdcHjQ , GddWja GdNHjQ , GdMcje ai GdJOHjQ hGdJbOjQ s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg (B[ (3HYfhGf (B: (3bGd GdeHQO ai GdcGed (B: (3hLGA ai GdMOjK Cf YdjkG Jdi HMVQJg (B" (3bd gd ffHFce HGdCNSQjf CYeGdkG (B] (3bhdg (B: (3aScJ GHf GdchG hYGO Ydi Edi bQGAGJg s
(3GdfSNI HgG MhGTs
(3cJH GdJQbje hHYV GdYfGhjjf HGdMeQIs
(3Ydi MhGTjgG HYV GdJYdjbGJ s
(3JHUQI GdYfhGf (B:s
(3LeY s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs